Helping the Poor : the IMF's New Facilities for Structural Adjustment - Landell-Mills, Joslin (Washington, D.C. : International Monetary Fund, 1992)
This paper discusses the IMF's New Facilities for Structural Adjustment (SAF) for helping the poor. The first arrangement supported by the SAF was approved by the IMF's Executive Board in August 1986. By the end of February 1992, 35 countries had already used resources under SAF arrangements and 19 under enhanced structural adjustment facility arrangements. For several of these, donors have used the policy framework paper as a basis for deciding their own loan commitments. It is hoped that the IMF's part in the international effort to deal with the crisis in the poorest countries will make an effective contribution to improving their well-being in a sustainable way.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet